Preservation of fallopian tubes in ectopic pregnancy (Texas Journal of Medical Science, 2023)
This study covers the application of laparoscopic partial tubal resection with end-to-end anastomosis can reduce the incidence of persistent ectopic pregnancy. In a normal pregnancy, the fertilised egg spends 4 to 5 days travelling down the fallopian tube before moving to the cavity of the uterus where it implants about 6 to 7 days after being fertilised. Most, but not all, ectopic pregnancies take place in the fallopian tube. Early detection of an ectopic pregnancy can prevent serious medical complications and may save the fallopian tube from permanent damage.